2021
DOI: 10.3389/fphar.2021.799588
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of siRNA Using Functionalized Gold Nanorods Enhances Anti-Osteosarcoma Efficacy

Abstract: Gold nanorods (GNRs) are intensively explored for the application in cancer therapy, which has motivated the development of photothermal therapy (PTT) multifunctional nanoplatforms based on GNRs to cure osteosarcoma (OS). However, the major limitations include the toxicity of surface protectants of GNRs, unsatisfactory targeting therapy, and the resistant effects of photothermal-induced autophagy, so the risk of relapse and metastasis of OS increase. In the present study, the GNR multifunctional nanoplatforms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Although PTT‐GT has been demonstrated to be effective in treating osteosarcoma when activated under NIR‐I irradiation, [ 193 ] treating osteosarcoma involving PTGNCs using gene‐photothermal therapy under NIR‐II activation would be more efficient due to the superior deep tissue penetration properties required to treat this type of cancer, which occurs deep within the skeletal system. Most recently, Luo et al.…”
Section: Application Of Ptgncs For Anticancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PTT‐GT has been demonstrated to be effective in treating osteosarcoma when activated under NIR‐I irradiation, [ 193 ] treating osteosarcoma involving PTGNCs using gene‐photothermal therapy under NIR‐II activation would be more efficient due to the superior deep tissue penetration properties required to treat this type of cancer, which occurs deep within the skeletal system. Most recently, Luo et al.…”
Section: Application Of Ptgncs For Anticancer Treatmentmentioning
confidence: 99%
“…Despite being a rare cancer that accounts for less than 0.2% of all cancers, [191] the development of new therapies for osteosarcoma has been called for, as the 5year survival rate for osteosarcoma patients has plateaued and remains far from optimistic since the establishment of the standard therapy of surgery and chemotherapy in the 1980s. [192] Although PTT-GT has been demonstrated to be effective in treating osteosarcoma when activated under NIR-I irradiation, [193] treating osteosarcoma involving PTGNCs using gene-photothermal therapy under NIR-II activation would be more efficient due to the superior deep tissue penetration properties required to treat this type of cancer, which occurs deep within the skeletal system. Most recently, Luo et al [180a] conducted a study where they prepared FePS 3 nanosheets (FePS NSs), belonging to metal phosphorus chalcogenides (MPX 3 ) with a wide bandgap, and found that they exhibited strong absorption in the NIR-II window.…”
Section: Osteosarcomamentioning
confidence: 99%
“…Moreover, they showed that TFEB silencing using this platform could effectively prevent osteosarcoma cells from metastasizing to the lungs, which was important because TFEB is linked to autophagy and encourages the spread of cancer. 66 Thus, these studies further validated the remarkable synergistic effects between phototherapy and nucleic acid-mediated gene delivery. Collectively, the aforementioned bimodal therapies showed improved efficacy over monotherapy.…”
Section: Nanoplatforms For Bimodal Therapiesmentioning
confidence: 67%
“…For example, gold nanorods-based GNR@siRNA/CPP, MoS 2 -PEG-PEI and WS 2 @PEI nanoplatforms are developed to treat osteosarcoma by the combination of PTT and gene therapy. [20][21][22] However, the non-biodegradability of this kind of nanomaterials induces them cannot be excreted naturally, which brings potential in vivo toxicities. As a new family of 2D nanomaterials, metal phosphorus chalcogenides (MPX 3 ) such as FePS 3 and FePSe 3 nanosheets which have a wide bandgap and exhibit a strongly absorption in the second window of near-infrared (NIR-II, 1000-1350 nm) light have been recently reported to serve as PTT agents.…”
Section: Introductionmentioning
confidence: 99%